Online Female Escort Advertisements: The Cost of Sex. (20th May 2016) - Griffith, James D.; Capiola, August; Balotti, Brandon; Hart, Christian L.; Turner, Ryan
Female escorts represent an occupational group that charges a fee for sex, which can be regarded as an extreme form of short-term mating. The present study examined if the fees charged by escorts are related to traits typically associated with female short-term mate value. A total of 2, 925 advertisements for female escorts offering sexual services in the United States were examined, as a customized software program was used to download all the advertisements from an online escort directory. The advertisement content was coded, and relationships between advertised physical characteristics and the hourly rate charged by female escorts were examined. The analyses showed that higher fees were associated with female escorts who advertised a waist-to-hip ratio near 0.7, lower weight and body mass index, younger age, and photographic displays of breast and buttocks nudity. The findings provide evidence that evolutionarily relevant traits associated with female short-term mate value are systematically related to fees charged for sexual services.